CANDELS multi-wavelength catalogs: source identification and photometry in the CANDELS COSMOS survey field - Nayyeri, H.; Hemmati, S.; Mobasher, B.; Ferguson, H.C.; Cooray, A.; Barro, G.; Faber, S.M.; Dickinson, M.; Koekemoer, A.M.; Peth, M.; Ashby, M.L.N.; Salvato, M.; et al. (American Astronomical Society, 2017)
We present a multi-wavelength photometric catalog in the COSMOS field as part of the observations by the Cosmic Assembly Near-infrared Deep Extragalactic Legacy Survey. The catalog is based on Hubble Space Telescope Wide Field Camera 3 (HST/WFC3) and Advanced Camera for Surveys observations of the COSMOS field (centered at R.A.: 10h00m28s, Decl.:+02h12m21s). The final catalog has 38671 sources with photometric data in 42 bands from UV to the infrared (~0.3-8 μm). This includes broadband photometry from HST, CFHT, Subaru, the Visible and Infrared Survey Telescope for Astronomy, and Spitzer Space Telescope in the visible, near-infrared, and infrared bands along with intermediate- and narrowband photometry from Subaru and medium-band data from Mayall NEWFIRM. Source detection was conducted in the WFC3 F160W band (at 1.6 μm) and photometry is generated using the Template FITting algorithm. We further present a catalog of the physical properties of sources as identified in the HST F160W band and measured from the multi-band photometry by fitting the observed spectral energy distributions of sources against templates.